SISTEM INFORMASI CUTI PADA BADAN NARKOTIKA NASIONAL KABUPATEN BLITAR - Linda Suvi Rahmawati; Jauharul Maknunah; Eni Farida; Himatus Yulva Aprilia Sari (Sekolah Tinggi Manajemen Informatika & Komputer PPKIA Pradya Paramita Malang, 2022)
The National Narcotics Agency (BNN) of Blitar Regency is a non-ministerial government agency (LKPH). In the field of employee licensing, there are delays in the technology sector, namely when doing permits, they still use manuals. Employees must apply for a permit through the procedures of several heads of related fields and must come to the office. So to assist the process of this leave permit, BNN improves the employee permit information system including leave by using android. Android is a smartphone operating system that provides an open platform for developers to create their applications with various versions of Android that suit the needs of Android users. Smarthpone is a mobile phone with a built-in processor, memory, screen and modem. From the results of the analysis, it was found that there are several parts in the BNN Blitar Regency licensing that require an android-based process to make it easier for employees to take leave permission without having to do it in the office.